Pengaruh Kualitas Pelayanan, Lokasi Dan Harga Terhadap Kepuasan Konsumen (Studi Kasus pada Konsumen Teman Kopi Malang) - Surya Dio Alby Wicaksono; Muhammad Ridwan Basalamah; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The culinary industry in Indonesia has developed since the early 2000s, giving rise to intense competition in the industry. The number of businesses that have sprung up has resulted in an increase in the number of similar businesses causing increasingly fierce competition. To deal with such situations and conditions, business actors are required to be quick and responsive in making decisions so that the businesses they establish can develop well. This study aims to determine how the influence of service quality, location and price on customer satisfaction, the effect of service quality on customer satisfaction, the effect of location on customer satisfaction and the effect of price on customer satisfaction.This study uses a qualitative approach. The population in this study were consumers of Kedai Teman Kopi Malang. The sample in this study was 75 respondents obtained from the results of calculations using the Slovin formula. The variables in this study are Service Quality (X1), Location (X2), Price (X3) and Consumer Satisfaction (Y). The data analysis method used is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear analysis, hypothesis testing and coefficient of determination with the help of SPSS 20.0 software for windows.The results showed that Service Quality, Location and Price Simultaneously Affect Consumer Satisfaction. Service Quality Partially Affects Consumer Satisfaction. Location Partly Affects Consumer Satisfaction. Price Partly Affects Consumer Satisfaction. Keywords: Service Quality, Location, Price and Consumer Satisfaction